Omalizumab for STAT3 Hyper-IgE Syndromes in Adulthood: A Case Report and Literature Review - Lan, Jun; Zhang, Yi; Song, Min; Cai, Shan; Luo, Hong; OuYang, Ruoyun; Yang, Pan; Shi, Xiaoliu; Long, Yingjiao; Chen, Yan (Frontiers in Medicine, 2022)
Background: Hyper IgE syndrome (HIES) is a primary immune deficiency syndrome characterized by elevated serum IgE, eczema, and recurrent skin and respiratory tract infections, and may also be accompanied by some connective tissue and skeletal abnormalities. According to the different genetic modes, it can be divided into autosomal dominant heredity (AD-HIES) and autosomal recessive heredity (AR-HIES). Currently, there is no complete cure or targeted treatment for HIES. Omalizumab is a humanized recombinant monoclonal antibody against IgE, reducing the level of free IgE, inhibiting the binding of IgE to receptors on the surface of effector cells, reducing the activation of inflammatory cells and the release of multiple inflammatory mediators. However, the effect of omalizumab in treating HIES remains unknown. Herein, we describe a case of a patient with AD-HIES treated with omalizumab with optimistic efficacy. Case presentation: A 28-year-old Chinese woman was admitted with manifestations including markedly elevated serum IgE level and recurrent pneumonia caused by multiple pathogens, such as pneumocystis jirovecii, cytomegalovirus, staphylococcus aureus, aspergillus, and mycobacterium tuberculosis. She had ever been suffered eczema-dermatitis, skin abscess, slightly traumatic fracture since childhood and was developed asthma and allergic bronchopulmonary aspergillosis lately. Using whole-exome sequencing, the STAT3 (c.1294G>T, p.Val432Leu) missense mutation for the autosomal dominant hyper-IgE syndrome was identified and omalizumab was prescribed as 300mg every two weeks. The patient responded well with an improvement of respiratory symptoms and serum IgE levels have decreased on follow-up. Conclusion: Omalizumab treatment not only provided a clinically important reduction in serum IgE and steroid requirement but also showed attenuated asthma symptoms, improved pulmonary function parameters and recurrent infections in patients with AD-HIES. Still, Larger scale prospective studies and long-term follow-up are required to establish the efficacy and safety of this therapeutic intervention.